OPTIMASI DIAMETER POROS RODA BELAKANG SEPEDA MOTOR - Aditya Husada; Stenly Tangkuman; Jotje Rantung (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
Interchangeability of motorcycles spare parts is needed in case of difficulty obtaining the original in the market. This research aims to develop the software model to optimize output shaft diameter and to compare the torque forwarded to rear sprocket of a motorcycle. The software develop using MATLAB R2010. Optimization is performed by making objective function variables with constraints and stress deflection resulted it the shaft loaded. Optimization is carried out with the conditioning in the highest speed transmission, that is : 1 840rpm, 2 1300rpm, 3 1800 rpm to 4 3000 rpm, and 5 3500rpm. Results obtained for a 8426.41 Nm/s power standard motorcycle is shaft diameter Do=12mm and Di=1.04mm. Finally, the software calculate the inertia force in order to obtain the stress Results showed that presence of shaft diameter optimization, load balance as well as engine power was still able to be borne on the optimum diameter. With the change of the diameter of the shaft diameter of the bearing replacement is done it is the same with the outer diameter of the shaft. Key word : rear wheel axle, Optimization, Do, Di.